La Vie Ouvrière : revue syndicaliste bi-mensuelle (Paris: [CGT])
"Periodiciteit: tweewekelijks Eerste nummer: 1909 Hoofdredactie: Pierre Monatte, Quai Jemmapes 96, Paris Redactie: F. Delaisi, J. Guillaume, J. Lapierre, G. Dumoulin, A. Rosmer, G. Airelle, A. Thierry Beheer: Quai Jemmapes 96, Paris Drukker/Drukkerij: Imprimerie Coopérative Ouvrière, Villeneuve-St.Georges (5 feb 1912) / Imp. Coopérative Ouvrière L'Universelle, Auxerre (5 okt 1913)"